Features of muscle function under load in individuals with flat feet - Germanova, K.V.; Kostyuchenko, V.F.; Germanova, A.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to examine the features of the function of lower extremity muscles and back muscles in flatfoot using EMG. Methods and structure of the study. The study was conducted in the laboratory of the Department of Physiology at the North-Western State Medical University named after I.I. Mechnikov, with 20 students aged 18–20 participating. The participants were divided into Group A and Group B, each consisting of 10 people. In Group A, the students had flat feet, while Group B consisted of students without flat feet. To assess muscle function, the Biopac Student Lab system was used to record muscle EMG, consisting of hardware (MP36/35/30 data acquisition unit, electrodes), BSL software (including PRO) and a laboratory manual. It is used to record and analyse muscle electrical activity during movement. The data, obtained from electrodes attached parallel to the muscle fibres, were recorded as a graph on a computer. Results and conclusions. The data obtained from the study showed that in the presence of flatfoot, the muscles of the posterior thigh, the gastrocnemius and the longissimus muscle are subjected to the greatest additional load during physical exertion. This finding highlights the importance of organising treatment and selecting appropriate methods and means for flatfoot prevention. Prevention of flatfoot is significantly more effective and accessible than its treatment. To strengthen the muscles and the joint-ligamentous apparatus of the feet, it is recommended to perform special exercises.